Leptin and insulin in young adulthood are associated with weight in infancy. Issue 2 (February 2020) - Simeoni, Umberto; Osmond, Clive; Garay, Ricardo; Buffat, Christophe; Boubred, Farid; Chagnaud, Christophe; Jouve, Elisabeth; Audebert, Christine; Antoine, Jean-Michel; Thornburg, Kent
Abstract : Low weight in early infancy is a known risk factor for cardio-metabolic syndrome in adult life. However, little is known either about developmental programming in subjects of normal birthweight or about events between the ages which separate early programming and the occurrence of disease at late adulthood. We tested the hypothesis that circulating concentrations of leptin, adiponectin and insulin in young, healthy adults, born with a birth size within the normal range, are influenced by early life growth patterns. In an observational study of 188 healthy volunteers aged 18–25 years (97 males, 91 females) we investigated the association of metabolic function with their birth size, their growth during childhood and their body composition. High plasma leptin in early adulthood, a risk factor for cardio-metabolic syndrome, was associated with low weight at age 2 years (correlation coefficient controlled for adult weight = −0.21, P  < 0.01). It was also positively associated with pre-prandial insulin and with HOMA (Homeostasis Model Assessment) insulin resistance. Leptin, leptin-adiponectin ratio and insulin correlated with lean mass, fat mass and percent fat ( P  < 0.0001). In conclusion, high leptin in early adulthood was associated with both low weight at age 2 years and insulin resistance. We speculate that high leptin is developmentally programmed and can contribute to the association between low weight in early infancy and increased cardio-metabolic risk in adulthood in healthy subjects.